Teknik Negosiasi dan Komunikasi Bisnis: Solusi Efektif Mengatasi Konflik dan Meningkatkan Kinerja Berdasarkan Study Literatur Review - Nofiyanti -; Masduki Asbari; Andira Fajrin; Dian Ayunita (Yayasan Aya Sophia Indonesia, 2025)
Increasingly competitive in the business world, effectiveness is required regarding key factors in building effective and sustainable cooperation, which in this case requires communication and negotiation skills. This research aims to analyze negotiation techniques and business strategies that can increase the success of a company. The author uses literature study from various relevant literature on negotiation techniques and business communication. The results showed that open communication and structured negotiations can help resolve conflicts, strengthen relationships between partners, and increase customer trust and loyalty. An effective negotiation process consists of the stages of planning, preparation, gathering information, presenting offers, and reaching a final agreement. The implementation of digital media, practical simulations, interpersonal approaches, and creativity in digital marketing are also proven to contribute to building more dynamic business communication. It can be concluded that the success of a business is greatly influenced by good communication and negotiation skills, which not only play a role in reaching mutually beneficial agreements, but also in creating productive and harmonious long-term relationships.